The seasonality experiment: Investigating how seasons affect the burning conditions of cremations. - Elisavet Stamataki; Guy De Mulder; Rosalie Hermans; Martine Vercauteren; Christophe Snoeck (PLoS ONE)
This study investigates the influence of seasons and weather conditions on cremation processes, using experimental archaeology and advanced analytical techniques. Four outdoor cremation experiments were conducted across different seasons in Greece, during which the four fleshed legs (front and hind) of the same domestic pig (Sus scrofa) were burned. The study highlights the effects of variables such as temperature, dryness of fuelwood, atmospheric pressure, and precipitation on the structural and chemical composition of burned bones. Results demonstrate a strong correlation between burning conditions and isotopic (δ13C, δ18O) as well as infrared indices (Infrared Splitting Factor (IRSF), Carbonyl-to-Carbonate ratio (C/C)), which are temperature-related. Comparisons with archaeological data from Belgium reveal potential seasonal patterns in past cremation practices. The findings underscore the need for expanded experimental research in various geographical areas with different altitudes and weather conditions to further investigate how the location in which burning was performed in combination with weather conditions affected the cremation settings and therefore past funerary practices.